(Un-)Bestimmte Zeichen Literarisch-musikalische Medienkombinationen bei Heinrich Wilhelm von Gerstenberg - Kummer, Ursula (Litterae, 2021)
Clear conceptual sharpness-distinctness: that is the strength of language. Where the clearly defining mind reaches its limits, conceptual confusion and poetic potential arise. To make such ideas nevertheless semiotically graspable and aesthetically usable, an indistinct medium is needed. Music seems particularly suitable for this. This is especially of interest in relation to the 18th century, the age of aesthetics and sentimentalism. Gerstenberg's examination of overlapping literary and musical media concepts and genres is an attempt to make the impossible poetically possible: To combine the distinctness of language with the indistinctness of music and thus to make the aporia of 'certain sentiments' tangible.